Frivillighed - velfærdsstatens redning? En etnologisk undersøgelse af inddragelsen af frivillige civilsamfundsaktører i Københavns kommunes ældrepleje - Kristensen, Nanna Simone; Mangerel, Jon Alexander; Søegaard, Rebecca (Culture and History: Student Research Papers, 2022)
In this paper, we investigate the collaborative work between three Danish nursing homes and the Copenhagen Municipality’s Administration for Health and Caregiving, in involving volunteers in the activities of the residents in the nursing homes. Changes in demographics have led to discussions among authorities and in public debates about alternatives to the historically professionalized welfare services, and to increase the degree of volunteerism as a measure for handling this development. We analyze the collaborations with Susan Leigh Star’s concept of invisible work and the ethnological State and Life-mode Theory and Niels Jul Nielsen’s notion of civil servant life-mode. We show how the invisible work being done is the prerequisite for the volunteer work, and how further integration of volunteerism in the welfare requires new forms of volunteerism, as volunteers may in practice be handling tasks that are currently being handled by welfare professionals. This turns out to be problematic, as volunteering seems to thrive in the space between unspokenness and a formalized framework.